Report of Tuckerella pavoniformis (Acari: Tuckerellidae) on Mamey, Mammea americana (Calophyllaceae), in Northwestern Peru - Escobar García, Héctor Alonso (2022)
The family Tuckerellidae, or peacock mites, is a monogeneric group comprising approximately 32 species, which are usually collected from the fruits or woody parts of their host plants. Fruits and branchlets of mamey, Mammea americana L. (Calophyllaceae) trees in north-western Peru were sampled for peacock mites throughout spring and summer for two consecutive years. This is the first record of Tuckerella pavoniformis (Ewing) (Acari: Tuckerellidae) feeding on mamey. Aggregations of mites were much higher and more common on the fruit epicarps than on branchlets. Recommendations for the development of an Integrated Pest Management strategy for this peacock mite are included.